G421 Evidence-based management of tics in children with adhd. (24th May 2017) - Ogundele, MO; Ayyash, HF; Skeete, I
Abstract : Aims: We aimed to provide a summary of best practice and published evidence for the management of tic disorders in children and adolescents with ADHD. Background: ADHD is the most common neurodevelopmental disorder in children and adolescents with in developed countries. Up to 20% ADHD patients have a Tic disorder. There is conflicting evidence of the role of psychostimulants in either precipitating or exacerbating tics in ADHD patients. Tics naturally wax and wane in clinical severity and are exacerbated by stress (e.g., consequences of untreated ADHD). It is often difficult to attribute blame to treatment. Method: We also carried out a literature review relating to the management of tic disorders in children and adolescents with ADHD. We performed a comprehensive search of Medline, EMBASE, CINAHL and Cochrane databases. No quantitative synthesis (meta-analysis) was deemed appropriate. Results: Meta-analysis of controlled trials does not support an association between new onset or worsening of tics and psychostimulant use. Apparent worsening or new onset of tics during ADHD treatment is oftentimes due to the coincidental waxing and waning natural history of tics. It is best to persevere for a few weeks with stimulant treatment if it is effectively controlling the ADHD symptoms and in most cases the tics will gradually subside. Nonetheless, stimulants may exacerbate tics in individual cases. Level A of evidence supported the use of noradrenergic agents (clonidine). Reuptake inhibitors (atomoxetine) and stimulants (methylphenidate) could be, also used for the treatment of Tics and comorbid ADHD. Aripiprazole resulted in an effective treatment for Tics, but it was only moderately effective on co-occurring ADHD symptomatology. Conclusion: The incidence of tic disorders and the severity of tics are not increased by the use of stimulants in paediatric patients treated with for ADHD. For patients with pre-existing tic disorders, the usual recommended dosing of stimulants should be used because supratherapeutic doses of this class of medications, specifically dextroamphetamine, have been shown to exacerbate tic disorders. If tics are disabling, stimulants could be substituted or complemented with Clonidine, or trial of non-stimulant Atomoxetine considered. Antipsychotics should be reserved for the most severe and uncontrollable tic disorders.